Building Agency Capacity for Trauma-Informed Evidence-Based Practice and Field Instruction. Issue 2 (3rd March 2016) - Strand, Virginia; Popescu, Marciana; Abramovitz, Robert; Richards, Sean
Abstract : Through this article the authors describe how schools of social work offering a child and adolescent trauma specialization actively partnered with their community-based field placement agencies to achieve a dual purpose: help agencies sustain the capacity for evidence-based trauma treatment (EBTT) and provide sufficient EBTT MSW student field placement sites that support preparation of trauma-informed practitioners by schools of social work. Development and description of the specific conceptual framework used to inform the trauma-informed organizational change initiative is described. Results of an Organizational Readiness assessment undertaken at six agencies reflect a strong alignment between implementation drivers identified in the literature (Fixsen, Blase, Naoom, & Wallace, 2009) and the conceptual framework. The manner in which these results are being used by schools of social work and their agency partners in sustaining the implementation of evidence-based trauma treatment is reviewed, and implications for future research, education, and practice is discussed.